Brain Natriuretic Peptide and Its Biochemical, Analytical, and Clinical Issues in Heart Failure: A Narrative Review - Fu, Shihui; Ping, Ping; Zhu, Qiwei; Ye, Ping; Luo, Leiming (Frontiers in Physiology, 2018)
Heart failure (HF) is a primary cause of morbidity and mortality worldwide. As the most widely studied and commonly applied natriuretic peptide, B-type natriuretic peptide (BNP) has the effects of diuresis, natriuresis, vasodilation, anti-hypertrophy and anti-fibrosis and it inhibits the renin-angiotensin-aldosterone and sympathetic nervous systems to maintain cardiorenal homeostasis and counteract the effects of HF. Both BNP and N-terminal pro B-type natriuretic peptide (NT-proBNP) are applied as diagnostic, managing and prognostic tools for HF. However, due to the complexity of BNP system, the diversity of BNP forms and the heterogeneity of HF status, there are biochemical, analytical and clinical issues on BNP not fully understood. Current immunoassays cross-react to varying degrees with pro B-type natriuretic peptide (proBNP), NT-proBNP and various BNP forms and cannot effectively differentiate between these forms. Moreover, current immunoassays have different results and may not accurately reflect cardiac function. It is essential to design assays that can recognize specific forms of BNP, NT-proBNP and proBNP to obtain more clinical information. Not only the processing of proBNP (corin/furin) and BNP (neprilysin), but also the effects of glycosylation on proBNP processing and BNP assays, should be targeted in future studies to enhance their diagnostic, therapeutic and prognostic values.